Method for preparing polyvinylidene fluoride ferroelectric nanoparticles

By performing interfacial nanoself-assembly in an aqueous mixture, PVDF ferroelectric nanoparticles with high β-phase content and narrow particle size distribution were prepared, which solved the problem that PVDF materials in the prior art is difficult to prepare nanostructures and control β-phase, and achieved efficient nanoparticle preparation and ferroelectric performance improvement.

CN119875155APending Publication Date: 2025-04-25SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411927445.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, PVDF materials are mainly one-dimensional and two-dimensional structures. There are difficulties in the preparation of zero-dimensional nanostructures (such as nanoparticles) and control of β crystal phases, and it is difficult to produce on a large scale.

Method used

By preparing a polyvinylidene fluoride (PVDF) solution and performing interfacial nano-self-assembly in an aqueous mixture, polyvinylidene fluoride ferroelectric nanoparticles are formed, and the crystalline phase of PVDF is controlled to improve ferroelectric properties.

Benefits of technology

The preparation of PVDF ferroelectric nanoparticles with narrower particle size distribution and high β-phase content is achieved, which improves its ferroelectric performance and thermal stability, and is suitable for mass production of high-performance electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209556840000071
    Figure BDA0005209556840000071
  • Figure BDA0005209556840000081
    Figure BDA0005209556840000081
Patent Text Reader

Abstract

The invention discloses a method for preparing polyvinylidene fluoride ferroelectric nanoparticles, which comprises the following steps of: preparing a polyvinylidene fluoride solution I which is an organic solvent; and injecting an organic solvent and an aqueous solvent from the bottom of the polyvinylidene fluoride solution I, and standing to obtain the polyvinylidene fluoride ferroelectric nanoparticles formed by interface nano self-assembly. The particle size of the polyvinylidene fluoride ferroelectric nanoparticles prepared by the method provided by the invention can reach 70 nm or below, the size distribution is relatively narrow, the ferroelectric phase content can reach 95% or above, and the polyvinylidene fluoride ferroelectric nanoparticles have good thermal stability and have a relatively good application prospect in the field of dielectric materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dielectric material preparation, and in particular to a method for preparing polyvinylidene fluoride ferroelectric nanoparticles. Background Art

[0002] Compared with traditional inorganic ferroelectric materials, ferroelectric polymers have the advantages of low cost, light weight, good flexibility and easy preparation. Among all ferroelectric polymers, polyvinylidene fluoride (PVDF) homopolymer and its copolymers have been widely studied due to their excellent piezoelectricity, pyroelectricity and ferroelectricity.

[0003] Compared with copolymers, PVDF homopolymer has many advantages, including large intrinsic polarization, high Curie temperature, high breakdown strength and low cost. PVDF has three common crystalline phases: α, β and γ phases. Among them, the β phase and the γ phase have non-zero net dipole moments, which is the reason why PVDF materials show ferroelectricity. Therefore, enhancing these two ferroelectric phases, especially the β phase, and suppressing the α phase is a long-term goal to improve its application performance.

[0004] So far, many methods have been applied to obtain the ferroelectric enhanced β phase, including mechanical deformation, corona poling, casting from highly polar solvents, incorporation of nanomaterials, random copolymerization with comonomers (such as trifluoroethylene, TrFE), etc. However, these methods have problems such as low efficiency, complex processes or deterioration of material properties. At the same time, in PVDF ferroelectric electronic devices (such as memory), miniaturization is effective for high-density storage and low-voltage operation. Miniaturization requires simultaneous manipulation of the formation of nanostructures and the enhancement of the ferroelectric phase, which is very challenging. Summary of the invention

[0005] In view of the above technical problems, the present invention provides a method for preparing polyvinylidene fluoride ferroelectric nanoparticles to solve the problem that PVDF materials in the prior art are mainly one-dimensional and two-dimensional structures, and there are certain difficulties in the preparation of zero-dimensional nanostructures (such as nanoparticles) and the control of β-crystalline phase, which makes large-scale production difficult.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In one aspect, the present invention provides a method for preparing polyvinylidene fluoride ferroelectric nanoparticles, comprising the following steps:

[0008] Step 1, preparing a polyvinylidene fluoride (PVDF) solution I; the solvent of the polyvinylidene fluoride solution I is an organic solvent;

[0009] Step 2: injecting an organic solvent and an aqueous solvent from the bottom of the polyvinylidene fluoride solution I, and allowing the solution to stand to obtain polyvinylidene fluoride ferroelectric nanoparticles formed by interfacial nano self-assembly.

[0010] As a preferred embodiment, in step 1, the concentration of the polyvinylidene fluoride solution I is 5 to 10 mg / mL.

[0011] As a preferred embodiment, the volume ratio of the polyvinylidene fluoride solution I to the organic solvent in step 2 is 2 to 4:1;

[0012] Preferably, the volume ratio of the polyvinylidene fluoride solution I to the aqueous solvent in step 2 is 1:4-8.

[0013] As a preferred implementation, in step 2, the standing time is 1 to 2 hours; in the technical solution of the present invention, during the standing process, phase separation of polyvinylidene fluoride occurs in the mixed system.

[0014] As a preferred embodiment, in step 1 and step 2, the organic solvent is selected from any one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), dimethylacetamide (DMAc) and triethyl phosphate (TEP);

[0015] Preferably, the organic solvents in step 1 and step 2 are the same.

[0016] As a preferred embodiment, in step 2, the aqueous solvent is water or a mixed solvent of water and alcohol;

[0017] Preferably, the aqueous solvent is a solvent having a volume ratio of water to alcohol of 1:0 to 3;

[0018] Preferably, the alcohol solvent is selected from any one of methanol, ethanol and isopropanol.

[0019] In certain specific embodiments, in step 2, the polyvinylidene fluoride ferroelectric nanoparticles are obtained from the mixed system after standing by centrifugation.

[0020] As a preferred embodiment, step 2 further includes a reprecipitation step;

[0021] Preferably, the reprecipitation step is: preparing a solution of polyvinylidene fluoride ferroelectric nanoparticles, adding the solution dropwise into water under stirring, continuing stirring and then standing, and finally centrifuging, washing and drying;

[0022] Preferably, the solvent of the solution is selected from any one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), dimethylacetamide (DMAc) and triethyl phosphate (TEP);

[0023] Preferably, the stirring speed is ≥2000rpm;

[0024] Preferably, the concentration of the solution is 5 to 10 mg / mL;

[0025] In the technical solution of the present invention, the polyvinylidene fluoride ferroelectric nanoparticles have a narrower particle size distribution range after being reprecipitated.

[0026] In another aspect, the present invention provides polyvinylidene fluoride ferroelectric nanoparticles prepared by the above method.

[0027] In the technical solution of the present invention, the polyvinylidene fluoride ferroelectric nanoparticles prepared by the above method have a β phase and have better ferroelectric properties.

[0028] In another aspect, the present invention provides the use of the polyvinylidene fluoride ferroelectric nanoparticles in preparing a dielectric energy storage capacitor.

[0029] The beneficial effects brought about by the technical solution provided by the present invention include:

[0030] 1. The method of the present invention can effectively control the size and morphology of PVDF ferroelectric nanoparticles by adjusting the ratio of water and alcohol solvent in the aqueous mixture and controlling the process conditions in the preparation process, thereby obtaining PVDF spherical nanoparticles of different particle sizes. The particle size of the final PVDF ferroelectric nanoparticles can reach less than 70 nm, and the size distribution is relatively narrow, which has good application prospects.

[0031] 2. The PVDF ferroelectric nanoparticles provided by the present invention have a relatively high main ferroelectric phase β phase in the crystalline phase, and the ferroelectric phase content can reach more than 95%, which is significantly better than the PVDF ferroelectric nanoparticles prepared by the traditional method;

[0032] 3. Compared with the original PVDF, the polyvinylidene fluoride ferroelectric nanoparticles prepared by the present invention maintain the original thermal stability, and the initial decomposition temperature is as high as 420°C, which meets the application requirements in high temperature environments and is conducive to improving its service life;

[0033] 4. The method provided by the present invention does not require complicated equipment or high-temperature treatment, and can be achieved only by controlling the mixing of the solvent and the non-solvent and simple stirring operations. It has the advantages of simple and easy operation, high preparation efficiency, low preparation cost, etc., and is conducive to large-scale and commercial promotion and application. DETAILED DESCRIPTION

[0034] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0035] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0036] The PVDF added in this embodiment and the comparative example is PVDF (M n ~71000,M w ~180000) and purchased from Sigma-Aldrich.

[0037] Example 1

[0038] Step 1, dissolving 50 mg of PVDF powder in 10 mL of NMP solvent to prepare a mixed solution 1 with a concentration of 5 mg / mL;

[0039] Step 2, inject 2 mL of mixed solution 1 into a test tube, inject 0.5 mL of NMP solvent and 8 mL of water from the bottom of the test tube, and let stand for 2 hours to obtain mixed solution 2;

[0040] Step 3: Separate the obtained mixed solution 2 at a rotation speed of 10000 rpm for 15 min to collect the precipitate, wash it with water twice, and dry it under vacuum for 12 hours to obtain polyvinylidene fluoride ferroelectric nanoparticles.

[0041] Example 2

[0042] The difference between this embodiment and embodiment 1 is that in step 2, 8 mL of water is replaced by 8 mL of an aqueous mixed solvent having a volume ratio of water to ethanol of 3:1, and the rest is the same as embodiment 1.

[0043] Example 3

[0044] The difference between this embodiment and embodiment 1 is that in step 2, 8 mL of water is replaced by 8 ml of an aqueous mixed solvent having a volume ratio of water to ethanol of 1:3, and the rest is the same as embodiment 1.

[0045] Example 4

[0046] Step 1, dissolving 50 mg of PVDF powder in 10 mL of DMF solvent to prepare a mixed solution 1 with a concentration of 5 mg / mL;

[0047] Step 2, inject 2 mL of mixed solution 1 into a test tube, inject 0.5 mL of DMF solvent and 8 mL of an aqueous mixed solvent with a volume ratio of water to methanol of 1:2 from the bottom of the test tube, and let stand for 2 hours to obtain mixed solution 2;

[0048] Step 3: Separate the mixed solution 2 at a rotation speed of 6000 rpm for 15 min to collect the precipitate, wash it with water twice, and dry it under vacuum for 12 hours to obtain polyvinylidene fluoride ferroelectric nanoparticles.

[0049] Example 5

[0050] Step 1, dissolving 80 mg of PVDF powder in 10 mL of DMSO solvent to prepare a mixed solution 1 with a concentration of 8 mg / mL;

[0051] Step 2, take 1.25 mL of mixed solution 1 and inject it into a test tube, inject 0.5 mL of DMSO solvent and 8 mL of an aqueous mixed solvent with a volume ratio of water to isopropanol of 2:1 from the bottom of the test tube, and let it stand for 2 hours to obtain mixed solution 2;

[0052] Step 3: Separate the obtained mixed solution 2 at a rotation speed of 4000 rpm for 15 min to collect the precipitate, wash it with water twice, and dry it under vacuum for 12 hours to obtain polyvinylidene fluoride ferroelectric nanoparticles.

[0053] Example 6

[0054] Step 1, dissolving 100 mg of PVDF powder in 10 mL of TEP solvent to prepare a mixed solution 1 with a concentration of 10 mg / mL;

[0055] Step 2, take 1 mL of mixed solution 1 and inject it into a test tube, inject 0.5 mL of TEP solvent and 8 mL of an aqueous mixed solvent with a volume ratio of water to ethanol of 2:1 from the bottom of the test tube, and let it stand for 2 hours to obtain mixed solution 2;

[0056] Step 3: Separate the obtained mixed solution 2 at a rotation speed of 2000 rpm for 15 min to collect the precipitate, wash it with water twice, and dry it under vacuum for 12 hours to obtain polyvinylidene fluoride ferroelectric nanoparticles.

[0057] Example 7

[0058] The polyvinylidene fluoride ferroelectric nanoparticles obtained in Example 1 were further dissolved in NMP solvent to prepare a mixed solution 3 with a concentration of 5 mg / mL. The mixed solution 3 was added dropwise into water at a stirring speed of 6000 rpm for reprecipitation. The precipitate was collected by centrifugation at 2000 rpm for 15 min, washed twice with water, and dried under vacuum for 12 hours to obtain polyvinylidene fluoride ferroelectric nanoparticles.

[0059] Example 8

[0060] The polyvinylidene fluoride ferroelectric nanoparticles obtained in Example 2 were further dissolved in NMP solvent to prepare a mixed solution 3 with a concentration of 5 mg / mL. The mixed solution 3 was added dropwise into water at a stirring speed of 4000 rpm for reprecipitation. The precipitate was collected by centrifugation at 2000 rpm for 15 min, washed twice with water, and dried under vacuum for 12 hours to obtain polyvinylidene fluoride ferroelectric nanoparticles.

[0061] Example 9

[0062] The polyvinylidene fluoride ferroelectric nanoparticles obtained in Example 4 were further dissolved in DMF solvent to prepare a mixed solution 3 with a concentration of 5 mg / mL. The mixed solution 3 was added dropwise into water at a stirring speed of 3000 rpm for reprecipitation. The precipitate was collected by centrifugation at 2000 rpm for 15 min, washed twice with water, and dried under vacuum for 12 hours to obtain polyvinylidene fluoride ferroelectric nanoparticles.

[0063] Comparative Example 1

[0064] The difference between this comparative example and Example 1 is that in step 2, 8 mL of water is replaced by 8 mL of ethanol, and the rest is the same as Example 1.

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 1 is that in step 2, 8 mL of water is replaced by 8 mL of an aqueous mixed solvent having a volume ratio of water to ethanol of 1:4, and the rest is the same as Example 1.

[0067] Comparative Example 3

[0068] The difference between this comparative example and Example 7 is that the stirring speed of 6000 rpm is replaced by 1000 rpm, and the rest is the same as Example 7.

[0069] Comparative Example 4

[0070] The difference between this comparative example and Example 1 is that in step 2, 0.5 mL of NMP solvent is replaced by 0.5 mL of DMSO.

[0071] Comparative Example 5

[0072] The difference between this comparative example and Example 1 is that in step 2, 0.5 mL of NMP solvent and 8 mL of an aqueous mixed solvent with a volume ratio of water to ethanol of 3:1 are injected from the top of the test tube, that is, from the top of the mixed solution 1.

[0073] Comparative Example 6

[0074] The difference between this comparative example and Example 1 is that 0.5 mL of NMP solvent is not added in step 2.

[0075] Comparative Example 7

[0076] This comparative example uses untreated PVDF powder as a control.

[0077] Performance Testing

[0078] The performance of the polyvinylidene fluoride ferroelectric nanoparticles obtained in the examples and comparative examples was tested, and the experimental results are shown in Table 1.

[0079] 1. Particle morphology test:

[0080] The dispersion liquid (dispersant is water) of the polyvinylidene fluoride ferroelectric nanoparticles obtained in each example and comparative example was drop-casted on a HOPG substrate; after drying, platinum was sputtered under vacuum and the appearance was measured using a scanning electron microscope (SEM).

[0081] 2. Average particle size test:

[0082] The polyvinylidene fluoride ferroelectric nanoparticles obtained in each example and comparative example were added into water to prepare a uniform dispersion without bubbles, and the particle size distribution result and the average value of the particle size were observed by a laser particle size analyzer.

[0083] 3. Decomposition temperature test:

[0084] The polyvinylidene fluoride ferroelectric nanoparticles obtained in each example and comparative example were subjected to thermogravimetric analysis (TGA) by heating from 30°C to 1000°C at a heating rate of 10°C min-1 under argon atmosphere using a thermogravimetric analyzer (TGA instrument, Thermoplus TG8120; Rigaku Corporation).

[0085] 4. Crystallinity test:

[0086] The XRD spectrum was obtained by using an X-ray diffractometer, using a Cu Kα radiation source (λ=0.154 nm). The XRD spectrum of the polyvinylidene fluoride ferroelectric nanoparticles obtained in each embodiment and comparative example was collected in the range of 5-40°, with a scanning step length of 0.025° and a scanning time of 2 seconds per step.

[0087] Table 1

[0088]

[0089]

[0090] It can be seen from the above test results that the interfacial self-assembly behavior of PVDF is closely related to the composition of the aqueous solvent. In Comparative Example 1, when the water content is low, the interface is not clear, but macromolecular aggregates appear, and no nanoparticles are formed; as the water ratio increases, a membrane-wrapped nanoparticle structure is formed in Examples 1-9, and finally spherical nanoparticles with a narrow size distribution are obtained under pure water. The applicant speculates that the reason is that the interaction between water and polar organic solvents such as NMP, DMSO, and DMF affects the crystallization process of PVDF. Water as a non-solvent causes PVDF to phase separate, and the mutual solubility of ethanol and polar organic solvents such as NMP, DMSO, and DMF changes the properties of the system, thereby affecting the formation of nanostructures. When the alcohol content in the aqueous solvent is high, the characteristic peak of the non-ferroelectric phase α phase is obvious; as the water content increases, the α phase peak gradually weakens, and the β and γ phase related peaks are enhanced. When the water ratio is high, the total proportion of β and γ phases (ferroelectric phase proportion) can be as high as 96%. In Comparative Examples 1-4, the water content is too little, and the upper part of the water phase becomes unclear, indicating that PVDF has condensed. As the ethanol content in the aqueous solvent increases, the interface becomes unclear after the aqueous solvent is injected, and no clear interface of the PVDF particles can be observed when only ethanol is used as the aqueous solvent.

[0091] Embodiments 7-9 further demonstrate that the NMP-water interface helps to form the electroactive phase of PVDF, and the reprecipitation method effectively prepares PVDF nanoparticles with narrower average particle size and distribution, providing more possibilities for the miniaturization of non-volatile memory. PVDF nanoparticles do not decrease in thermal stability, while PVDF materials obtained by traditional processes (such as mechanical stretching and high-temperature thermal annealing) usually lose thermal stability. In addition, the preparation method involved in the present invention is simple, which is conducive to the mass production and application of PVDF nanoparticles in high-performance electronic equipment industries (such as non-volatile memory, energy harvesting devices and polymer nanocomposites).

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing polyvinylidene fluoride ferroelectric nanoparticles, characterized in that: The following steps are involved: Step 1, preparing a polyvinylidene fluoride solution I; the solvent of the polyvinylidene fluoride solution I is an organic solvent; Step 2: injecting an organic solvent and an aqueous solvent from the bottom of the polyvinylidene fluoride solution I, and allowing the solution to stand to obtain polyvinylidene fluoride ferroelectric nanoparticles formed by interfacial nano self-assembly.

2. The method according to claim 1, characterized in that In step 1, the concentration of the polyvinylidene fluoride solution I is 5 to 10 mg / mL.

3. The method according to claim 1, characterized in that The volume ratio of the polyvinylidene fluoride solution I to the organic solvent in step 2 is 2 to 4:1; Preferably, the volume ratio of the polyvinylidene fluoride solution I to the aqueous solvent in step 2 is 1:4-8.

4. The method according to claim 1, characterized in that In step 2, the standing time is 1 to 2 hours.

5. The method according to claim 1, characterized in that In step 1 and step 2, the organic solvent is selected from any one of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, dimethylacetamide and triethyl phosphate; Preferably, the organic solvents in step 1 and step 2 are the same.

6. The method according to claim 1, characterized in that In step 2, the aqueous solvent is water or a mixed solvent of water and alcohol; Preferably, the aqueous solvent is a solvent having a volume ratio of water to alcohol of 1:0 to 3; Preferably, the alcohol solvent is selected from any one of methanol, ethanol and isopropanol.

7. The method according to claim 1, characterized in that In step 2, the polyvinylidene fluoride ferroelectric nanoparticles are obtained from the mixed system after standing by centrifugation.

8. The method according to claim 1, characterized in that The method further comprises a reprecipitation step after step 2; Preferably, the reprecipitation step is: preparing a solution of polyvinylidene fluoride ferroelectric nanoparticles, adding the solution dropwise into water under stirring, continuing stirring and then standing, and finally centrifuging, washing and drying; Preferably, the solvent of the solution is selected from any one of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, dimethylacetamide and triethyl phosphate; Preferably, the stirring speed is ≥2000rpm; Preferably, the concentration of the solution is 5-10 mg / mL.

9. Polyvinylidene fluoride ferroelectric nanoparticles prepared by the method according to any one of claims 1 to 8.

10. Use of the polyvinylidene fluoride ferroelectric nanoparticles according to claim 9 in preparing a dielectric energy storage capacitor.